2024
DOI: 10.3390/buildings14051331
|View full text |Cite
|
Sign up to set email alerts
|

Waveform Complexity and Positioning Analysis of Acoustic Emission Events during the Compression Failure Process of a Rock Burst Prone Sample

Wenlong Zhang,
Jiajia Yu,
Xiufeng Xu
et al.

Abstract: The localization results of acoustic emission (AE) events can reflect the location and pattern of burst-prone rock failures. However, event localization heavily depends on the quality of the original waveform of the sensor. Therefore, this study analyzed the AE waveform of a rock sample under compression to evaluate its failure localization and quality. From the research results, it could be seen that the initial failure was relatively calm, with clear take-off points, which can be better used for accurate AE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…They explored the influence of freeze-thaw conditions on internal microcracks in sandstone through analysis of AE ring-down counts. Zhang W et al [15] pointed out that the localization results of AE events could effectively reflect the location and mode of fracture within rocks. They indicated that during initial failure, the events were small and dispersed, whereas during later failure, they were large and concentrated.…”
Section: Introductionmentioning
confidence: 99%
“…They explored the influence of freeze-thaw conditions on internal microcracks in sandstone through analysis of AE ring-down counts. Zhang W et al [15] pointed out that the localization results of AE events could effectively reflect the location and mode of fracture within rocks. They indicated that during initial failure, the events were small and dispersed, whereas during later failure, they were large and concentrated.…”
Section: Introductionmentioning
confidence: 99%